Pemberdayaan Perempuan (Kajian Tafsir Al-Qurâan Surah Al-Nisa Ayat 1) - Marwati, Marwati (Jurnal Adabiyah, 2015)
This writing aims at putting forward the kind of woman empowerment in al-Quran. In al-Quran, woman discourse becomes one of those main themes. The close attention of al-Quran to woman is reflected in Surah al-Nisa. This chapter leads us to understand more that it is not only a name of surah (chapter) or theme, but reflects to what extent God highly appreciates woman in her position. This article applied tahlili method in exploring the meaning of verses that come to conclusion that Al-Quran greatly and honorably appreciates woman in her field of position as long as she is still on the track of Godâs law.